Hospital Responsibilities for the Use of Covid-19 Handling Funds Based on a State Administrative Law Perspective - Maysarah, Maysarah (International Journal Reglement & Society (IJRS), 2020)
Hospitals as a device or component of health have responsibility for the funds for handling Corona Virus Disease (Covid-19) in Indonesia. During this pandemic, hospitals certainly play an important role for public health, especially those with Covid-19. The method used in this research is normative law research which combines the data obtained from library materials and then analyzed qualitatively. From the research results it is known that the Government is taking action quickly, precisely, and accurately in handling the Covid-19 pandemic. The government's steps in handling the Covid-19 pandemic were carried out by combining the use of statutory authority, policy regulations, actions of government agencies and officials, and bureaucratic support as a policy implementing organ. In handling the Covid-19 pandemic, the President took a policy by establishing a Government Regulation in Lieu of Law (Perppu) Number 1 of 2020 concerning State Financial Policy and Financial System Stability for Handling the Corona Virus Disease (Covid-19) Pandemic and / or in the Context of Facing Dangerous Threats National Economy and / or Financial System Stability on March 31, 2020. That the responsibility of the hospital is to use the funds for handling Covid-19 to provide medical devices related to prevention or treatment of Covid-19 such as PPE, test kits, reagents, ventilators, hand sanitizers and others